Stable hydrogen (dD) and carbon isotope (d13C) values of sedimentary terrestrial leaf wax from sediment core GIK17286-1 - Yiming V Wang; Thomas Larsen; Stefan Lauterbach; Nils Andersen; Thomas Blanz; Uta Krebs-Kanzow; Paul Gierz; Ralph R Schneider (PANGAEA, 2022)
We present stable hydrogen isotope (dD) and carbon isotope (d13C) of sedimentary terrestrial leaf wax, namely n-alkanes, from marine sediment core SO 188-17286-1 (Bay of Bengal, 19°44.58'N, 89°52.76'E, 1428 m water depth) for the last ~130 kyr. There are four different homologues (n-C27, n-C29, n-C31 and n-C33). The concentration data of each homologues are also present here. Identification and quantification (concentration) of the individual compounds was carried out with an Agilent 6890 Gas Chromatograph (GC) with a flame ionization detector in the Geoscience, University of Kiel. The d13C and dD values of n-alkanes were then analyzed at the Leibniz Laboratory for Radiometric Dating and Stable Isotope Research in Kiel University using an Agilent 6890 GC coupled with a Thermo Finnigan MAT 253 isotope ratio mass (IRMS).